2010
DOI: 10.1017/s0022029910000865
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal fermentation characteristics and fatty acid profile of ruminal fluid and milk of dairy cows fed flaxseed hulls supplemented with monensin

Abstract: Flaxseed hull, a co-product obtained from flax processing, is a rich source of n-3 fatty acids (FA) but there is little information on its value for dairy production. Monensin supplementation is known to modify biohydrogenation of FA by rumen microbes. Therefore, the main objective of the experiment was to determine the effect of feeding a combination of monensin and flaxseed hulls on ruminal fermentation characteristics and FA profile of ruminal fluid and milk. Four ruminally fistulated multiparous Holstein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…The low ammonia concentrations in both monensin groups are consistent with the protein-sparing effect and decreased ammonia concentrations reported in monensin-fed dairy cattle (Plaizier et al, 2000;Ghorbani et al, 2011) but no effects have also been observed (Ramanzin et al, 1997;da Silva-Kazama et al, 2011). Protein sparing can be beneficial to the host; however, as ammonia is required for microbial protein synthesis, a very low ammonia concentration could be detrimental, depending on the quality of protein spared.…”
Section: Discussionsupporting
confidence: 84%
“…The low ammonia concentrations in both monensin groups are consistent with the protein-sparing effect and decreased ammonia concentrations reported in monensin-fed dairy cattle (Plaizier et al, 2000;Ghorbani et al, 2011) but no effects have also been observed (Ramanzin et al, 1997;da Silva-Kazama et al, 2011). Protein sparing can be beneficial to the host; however, as ammonia is required for microbial protein synthesis, a very low ammonia concentration could be detrimental, depending on the quality of protein spared.…”
Section: Discussionsupporting
confidence: 84%
“…AlZahal et al (2008) detected an interaction between R and increasing the amount of soybean oil supplementation increasing the percentage of trans 18:1 and decreasing SMCFA in milk fat. In contrast, no R interaction occurred with feeding flaxeed (da Silva-Kazama et al, 2011). In our companion study (Reveneau et al, 2012), we reported that these same cows fed AV fat decreased milk fat yield by 0.08 kg/d without R, but AV fat decreased milk fat more (0.18 kg/d) when combined with R; in contrast, CNO severely depressed milk fat (>0.30 kg/d) regardless of R (R × source interaction, P < 0.10).…”
mentioning
confidence: 96%
“…The present study is part of a larger project with results on milk production, milk composition and concentration of the mammalian lignan enterolactone in the rumen and milk reported elsewhere (Petit et al 2009). Results on ruminal fermentation characteristics and fatty acid profile of milk fat and rumen fluid from the same study also are reported elsewhere (da Silva- Kazama et al 2011). Four lactating multiparous Holstein cows fitted with ruminal cannulas (10 cm, Bar Diamond Inc., Parma, ID, USA) averaging 665 ± 21 kg of body weight and 190 ± 5 days in milk at the beginning of the experiment were used in the experiment.…”
Section: Cows and Dietsmentioning
confidence: 81%
“…Monensin has been shown to increase concentration of conjugated linoleic acid (Bell et al 2006;da Silva-Kazama et al 2011) and to decrease those of saturated FA in milk fat of dairy cows. Although a combination of monensin and flaxseed hull supplementation may contribute to modify milk composition for better human health as shown by Silva- Kazama et al (2011) there is no information on the effect of feeding both monensin and flaxseed hulls on digestibility of fatty acids and nutrients. Therefore, the main objective of the experiment was to determine the effect of feeding diets supplemented or not with monensin and flaxseed hulls on total apparent tract digestibility of FA and nutrients.…”
mentioning
confidence: 99%